Pyrolysis performance, kinetic, thermodynamic, product and joint optimization analyses of incense sticks in N2 and CO2 atmospheres. (October 2019) - Wen, Shaoting; Yan, Youping; Liu, Jingyong; Buyukada, Musa; Evrendilek, Fatih
Abstract: Thermogravimetric and pyrolysis-gas chromatography/mass spectrometry analyses were performed to quantify the pyrolysis performances, kinetics, thermodynamics, products and optimization of incense sticks (IS) in N2 and CO2 atmospheres at five heating rates. The increased heating rate caused a lagged IS pyrolysis, moving its curves to a higher temperature. According to four model-free methods, activation energy estimates ranged from 34.17 to 439.19 kJ· mol −1 and 28.46–187.34 kJ· mol −1 in the N2 and CO2 atmospheres, respectively. The three-dimension diffusion (spherical symmetry) (D3) was determined using the Horowitz-Metzger method as the most probable degradation mechanism in both atmospheres. The main pyrolytic products were found as benzene and its derivatives whose mass accounted for 49.94% of the total 18 products. Significant two-way interaction effects were found between temperature, heating rate, and atmosphere type on the three responses of remaining mass, derivative thermogravimetry, and differential scanning calorimetry ( p  = 0.001). The best joint optimization was obtained at 899.5 °C with the heating rate of 5 °C·min −1 in the CO2 atmosphere and was more sensitive to the increased heating rate in the N2 than CO2 atmosphere. Highlights: Thermal behaviors of incense sticks(IS) in N2 and CO2 atmosphere were compared. The different volatilization performance of IS pyrolysis. Kinetic and thermodynamic parameters were applied to investigate the pyrolysis process. Py–GC/MS were used to study the pyrolysis products of IS. Significant two-way interactions were found and the best joint optimization was obtained.